KAJIAN MUSIKOLOGI MUSIK IRINGAN TARI JEPIN KERIS KARYA YUZA YANIS CHANIAGO - Ega Elpasa; Ismunandar Ismunandar; Asfar Muniir (Universitas Tanjungpura, 2018)
AbstractThe background of this research is to documenting the companion music of jepin dance, especially jepin keris dance. The general problem in this research are : How is the description of music accompanion of Jepin Keris dance by Yuza Yanis Chaniago?. The purpose of this research are : 1) Describe the music accompanion of Jepin Keris dance by Yuza Yanis Chaniago, 2) Describe the selodang melody on music accompanion of Jepin Keris by Yuza Yanis Chaniago, 3) Describe the beruas rythm pattern on music accompanion of Jepin Keris dance by Yuza Yanis Chaniago, 4) Describe the rebana rythm pattern on music accompanion of Jepin Keris dance by Yuza Yanis Chaniago, 5) Describe the implementation that will used in study process in School. The method that used in this research is explorative descriptive method and musicology approach. The data that contained in this research is the result from observation and interviews with the interviewer which were selodang melody pattern, beruas rythm pattern, and lyrics. The result of this research is music notation of Jepin Keris dance by Yuza Yanis Chaniago. This music accompanion of Jepin Keris dance by Yuza Yanis Chaniago has beruas notation, selodang notation, and also rebana notation and how to play it, that can be used as a guide to learn music of Jepin Keris by Yuza Yanis Chaniago. Keywords : Musicology Music Computation Dance of Jepin Keris By Yuza Yanis chaniago